Increasing Severity of Pneumoconiosis Among Younger Former US Coal Miners Working Exclusively Under Modern Dust-Control Regulations. Issue 6 (June 2017) - Graber, Judith M.; Harris, Gerald; Almberg, Kirsten S.; Rose, Cecile S.; Petsonk, Edward L.; Cohen, Robert A.
Abstract : Background: Coal workers' pneumoconiosis (CWP) steadily declined among US miners following dust control regulations in 1970. In 2000, severe forms of this disease reemerged among young miners, and are well described among working—but not former—miners. Methods: Black lung benefits program (BLBP) data (2001 to 2013) were used to estimate respiratory disease burden among former miners including: (1) CWP (simple; advanced CWP, and progressive massive fibrosis [CWP/PMF]); and (2) respiratory impairment (FEV1 percent reference: mild, moderate, ≥moderately-severe). Results: Among 24, 686 claimants, 8.5% had advanced CWP/PMF; prevalence was highest among younger (less than or equal to 56 years: 10.8%) and older (greater than 70 years: 8.4%) miners and those who began work after versus before 1970 (8.3% vs. 4.0%). Conclusions: BLBP claims provide potentially useful data for monitoring the burden and severity of coal mine dust lung disease, and assessing efficacy of protective regulations. Abstract : Supplemental Digital Content is available in the text